Challenges and opportunities for the resumption of nature tourism in post-pandemic Sri Lanka - Priyan Perera; Charitha Jayakody; Udeshika Jayapali; David Newsome (International Journal of Geoheritage and Parks, 2023)
Prior to COVID-19 heavy tourist pressure was causing environmental degradation and wildlife disturbance in Sri Lankan protected areas. The pandemic abruptly stopped visitation causing devastating impacts on the entire nature-based tourism sector. At the same time, the pandemic opened a window of opportunity to rethink the way the nature-based tourism is practiced in Sri Lanka's protected areas and bring it to the “sustainable track”. In this paper, we present a “position statement” to aid planning for sustainable and resilient nature-based tourism in post-pandemic Sri Lanka by validating and employing previous work on sustainable nature-based tourism planning, and information gathered through field observations and semi-structured interviews of nature-based tourism stakeholders in Sri Lanka. Future planning will require reflection and research with the aim of developing a more responsible and ethical approach to tourism activity and the viewing of wildlife. As the present economic and energy crisis is likely to prolong social and environmental difficulties, planning for a resilient nature-based tourism industry and appropriate community engagement is a priority.